PENDEKATAN MARKOV CHAIN UNTUK MENGANALISIS PERENCANAAN SUMBER DAYA MANUSIA DI KEPOLISIAN SEKTOR TAMALATE KOTA MAKASSAR - Suhartin M; Ruliana Ruliana; Muhammad Kasim Aidid (Universitas Negeri Makassar, 2021)
this research, an analysis of Human Resources planning in the Makassar City Tamalate Police Sector uses Markov Chain. The data used are sourced from secondary data in the Makassar City Tamalate Police Sector from the last two years period, from 2018 to 2019. The Markov Chain is used to find out transfers that occur between police positions with the first process being determining states, calculating inter-state probability values, forming a transition probability matrix, and predicting the number of police officers for the next six years. Based on the research conducted, it can be concluded that five states were formed, the ranks of the Second Police Brigadiers up to the Chief Police Brigadier are classified as Non-Commissioned Officers positions, state two the ranks of Second Police Inspector Adjutant up to First Pollice Inspector Adjutant are clarified as Warrant Officers position, state three Second Police Inspector up to Police Commissioner Adjutant are clarified Low-Rank Officers, four state Pollice Coommisioner are clarified of Mid Rank Officer, state five additional and reduction of Police Members. Based on the results of forecasting, the probability for the most Police Members in the year 2020 to 2025 is a member domiciled as a Non-Commissioned Officers, the probability of a large number of Non-Commissioned Officers is relatively stable at 0.54 from 2020 to 2024 and will decrease by 0.01 in 2025. Probabilities the number of Warrant Officers has increased quite dramatically, in 2020 amounting to 0.35 continues to increase until 2025 which is equal to 0.42. Whereas the probability for the number of Police Members to be Low-Rank Officers has decreased every year from 2020 to 0.08 to 0.03 in 2025. Then for Mid Rank Officers the probability for the number of Police Members to remain stable every year is 0.01. The probability of the number of Police officers in 2020 is 0.02 and in 2025 it is 0.01